PERISTILAHAN MENYUNAT ANAK PEREMPUAN MASYARAKAT MELAYU SAMBAS - Dina Misliati; Patriantoro Patriantoro; AR Muzammil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This study observed the activity of circumcise of Sambas Community daughters. Circumcise is a ritual tradition carried out hereditary by the community in pre-implementation, or post-implementation stage. The approach of this is the ethno-linguistics with the research problem in form of terminologi, lexical, meanings cultural, and its implementation in teaching and learning.The methodology used in this research was descriptive in form of qualitative research. The data sources of this study is the speech of Malay language in Sambas dialect spoken by community of Teluk Keramat sub-district, Kubangga village Kubung. The data in this study is the terminology used in  circumcises daughters of Sambas Malay community such as tools, process, and the terminology of speech.  The technique of this research is interview. the tools of dsts collection were interview guideline, stationary, camera, and recording devices. Based on the research,  conducted, 90 terms were collected as data of research. The data consist of 59 terms of tool, 17 terms of process, and 4 terms of time, 6 terms of doer, 3 terms of place,3 terms of word and 3 terms of abstinence forbids. Keywords:  Circumcising Daughters Terminology, Malay Sambas